Prevalence and influencing factors of anxiety and depression symptoms among the first-line medical staff in Wuhan mobile cabin hospital during the COVID-19 epidemic: A cross-sectional survey. Issue 21 (28th May 2021) - Zhang, Xiao-Bo; Xiao, Wei; Lei, Jing; Li, Ming-Xia; Wang, Xin; Hong, Yun-Jun; Xu, Ping; Sun, Juan
Abstract : Abstract: To investigate the prevalence of anxiety and depressive symptoms and the associated risk factors among first-line medical staff in Wuhan during the coronavirus disease 2019 (COVID-19) epidemic. From March 5 to 15, 2020, the Hamilton Anxiety Scale and Hamilton Depression scale were used to investigate the anxiety and depression status of medical staff in Wuhan Cabin Hospital (a Hospital). Two hundred seventy-six questionnaires were received from 96 doctors and 180 nurses, including 79 males and 197 females. During the COVID-19 epidemic, the prevalence rate of anxiety and depression was 27.9% and 18.1%, respectively, among 276 front-line medical staff in Wuhan. The prevalence rate of anxiety and depression among doctors was 19.8% and 11.5%, respectively, and the prevalence rate of anxiety and depression among nurses was 32.2% and 21.7%, respectively. Females recorded higher total scores for anxiety and depression than males, and nurses recorded higher scores for anxiety and depression than doctors. During the COVID-19 epidemic, some first-line medical staff experienced mental health problems such as depression and anxiety. Nurses were more prone to anxiety and depression than doctors. Effective strategies toward to improving the mental health should be provided to first-line medical staff, especially female medical staff and nurses.